New bias voltage generators for TFT-LCD's drivers - Hirata, Manabu; Suzuki, Yasoji; Yoshida, Masahiro; Arayashiki, Yutaka; Teramoto, Mitsuo; Choomchuay, Somsak (My University, 2000)
New positive and negative bias voltage generators for TFT-LCD's drivers utilizing charge pump circuits are introduced. The generators can generate positive or negative voltages with various amplitude by simply changing the number of pumping stages. By using the circuit simulation program HSPICE, it is demonstrated that the introduced generators can provide enough positive or negative voltages for TFT-LCD's drivers.
Keywords: Charge pump circuit; TFT-LCD; Voltage generator